Quality of life in Norwegian pregnant women and men with pregnant partners, and association with perception of sleep and depressive symptoms: a cross-sectional study - Malene Brekke; Amin Amro; Milada Cvancarova Småstuen; Kari Glavin; Beate Solberg; Anne-Martha Utne Øygarden; Kristin Marie Sæther; Trude Haugland (BMC, 2023)
Abstract Background Pregnant women and men with pregnant partners experience variations in quality of life (QoL) during pregnancy, a period characterized by physical, psychological, and social changes. Pregnancy is associated with reduced QoL, depressive symptoms, and sleep problems. This study aimed to: (1) determine whether Norwegian pregnant women and men with pregnant partners differed in QoL levels in the third trimester of pregnancy; (2) determine whether the relationship between perception of sleep and QoL is moderated by depressive symptoms, when analyzed separately in pregnant women and men with pregnant partners; and (3) determine whether selected possible predictive factors were associated with QoL when stratified by level of depressive symptoms, in pregnant women and men with pregnant partners separately. Methods A cross-sectional study conducted between October 2018 and January 2020 included 228 pregnant women and 197 men with pregnant partners in the third trimester of pregnancy. The age range was 22-50 years. QoL was assessed using the World Health Organization Quality of Life Questionnaire brief version, depressive symptoms using the Edinburgh Postnatal Depression Scale, and perception of sleep by a single item. Data were analyzed in SPSS version 28 using descriptive statistics, the PROCESS macro for moderation analyses, and multivariate linear regression. The level of statistical significance was p < 0.05. Results Pregnant women reported significantly lower QoL scores on the physical health and psychological domains than the men with pregnant partners. Our data did not reveal any moderating effect of depressive symptoms on the relationship between the perception of sleep and QoL. Depressive symptoms in the pregnant women were found to be a significant predictor of lower QoL in all domains. In the men with pregnant partners, getting enough sleep was a significant predictor of higher QoL in all domains. In the pregnant women without depressive symptoms, higher QoL in the physical health domain was significantly associated with the perception of getting enough sleep. Conclusion Women in the final trimester of pregnancy experience poor QoL compared to the men with pregnant partners. Pregnant women with depressive symptoms have lower QoL compared to those without depressive symptoms. The perception of getting enough sleep was associated with better QoL.